A Reference System Architecture with Data Sovereignty for Human-Centric Data Ecosystems - Simon Scheider; Florian Lauf; Frederik Möller; Boris Otto (Business & Information Systems Engineering, 2023)
Since the European information economy faces insufficient access to and joint utilization of data, data ecosystems increasingly emerge as economical solutions in B2B environments. Contrarily, in B2C ambits, concepts for sharing and monetizing personal data have not yet prevailed, impeding growth and innovation. Their major pitfall is European data protection law that merely ascribes human data subjects a need for data privacy while widely neglecting their economic participatory claims to data. The study reports on a design science research (DSR) approach addressing this gap and proposes an abstract reference system architecture for an ecosystem centered on humans with personal data. In this DSR approach, multiple methods are embedded to iteratively build and evaluate the artifact, i.e., structured literature reviews, design recovery, prototyping, and expert interviews. Managerial contributions embody novel design knowledge about the conceptual development of human-centric B2C data ecosystems, considering their legal, ethical, economic, and technical constraints.
Keywords: 000; Data ecosystems; Data sovereignty; Design science research; Personal data markets; Reference system architecture